Al-Gharar Wa Tathbiiqaatuhu Fil Mu'aamalaat Al-Maaliyyah Al-Mu'aashirah - Turaihan; DR. M. MUINUDINILLAH, DR. M. Muinudinillah (2016)
The Gharar and It's Applications in the Contemporary Financial Transactions This research (thesis) is submitted by the student Turaihan Tarmijan under the supervision of DR. Mu'inudinillah Bashri, MA. to obtain Master's degree in the Department of (Islamic Jurisprudence and Assets) Muhammadiyah University of Surakarta. This thesis aims to reveal the essence of gharar which becomes one of the factors in the violation of contract or transaction. This research is a document study with scientific analysis emphasizing on the application aspect of gharar in contemporary financial transaction. The research data was taken from classical and contemporary sources in the field of Islamic jurisprudence and assets. Contemporary financial transaction covers various forms and is never unknown previously in Islamic jurisprudence, for instance Multi Level Marketing (MLM) and insurance. However, not all of these financial transactions are halal or legal in Islamic law since there are factors which can violate the legality and harm one of or both parties having the transaction. In this case, one of the factors violating transaction is gharar. Gharar means uncertainty as in the case of effect, goods, characteristics and not knowing whether something can be obtained or not. Islamic jurisprudence ulama agree that gharar is haram and violates contract, but they give tolerance towards gharar which does not influence a contract because of necessity factor. In practice, a transaction can be called gharar transaction if it fulfills four conditions, namely (1) the transaction is pure financial transaction, not donation; (2) gharar becomes clear characteristics appearing in a transaction; (3) gharar is included in basic transaction; and (4) the transaction is not the only way to fulfill necessity. In the application of the four conditions above, it is found that there are a number of contemporary financial transactions indicated as gharar transaction, including trading-renting, lottery, telequiz using communication device, Multi Level Marketing (MLM) within one of its forms and conventional insurance. These five transactions are haram or illegal to be practiced because they clearly belong to pure financial transaction associated with gharar in their basic transaction and are not the only way to fulfill the necessity. Besides, Islam, in responding to the human life necessity, has provided alternative solution included in this thesis. Keywords: gharar, financial transaction, application .